Specification and Verification of Declarative Open Interaction Models A Logic-Based Approach - Montali, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Many novel application scenarios and architectures in business process management or service composition are characterized by a distribution of activities and resources, and by complex interaction and coordination dynamics. In this book, Montali answers fundamental questions on open and declarative modeling abstractions via the integration and extension of quite diverse approaches into a computational logic-based comprehensive framework. This framework allows non IT experts to graphically specify interaction models that are then automatically transformed into a corresponding formal representation and a set of fully automated sound and complete verification facilities. The book constitutes a revised and extended version of the author$1 (Bs PhD thesis, which was honored with the 2009 (3z(BMarco Cadoli(3y (Bprize, awarded by the Italian Association for Logic Programming for the most outstanding thesis focusing on computational logic, discussed between the years 2007 and 2009.s
I Specification -- Declarative Open Interaction Models -- The ConDec Language -- The CLIMB Rule-Based Language -- Translating ConDec into CLIMB -- Extending ConDec -- Related Work and Summary -- II Static Verification -- Static Verification of Declarative Open Interaction Models -- Proof Procedures -- Static Verification of ConDec Models with g-SCIFF -- Experimental Evaluation -- Related Work and Summary -- III Run-Time and A-Posteriori Verification -- Run-Time Verification -- Monitoring and Enactment with Reactive Event Calculus -- Declarative Process Mining -- Related Work and Summary -- IV Conclusion and Future Work -- Conclusion and Future Work.
Keywords: Computer science; Software engineering; Logic design; Information systems; Management information systems; Computer Science; Information Systems Applications (incl.Internet).; Logics and Meanings of Programs; Software Engineering; Business Information Systems; Computer Appl. in Administrative Data Processing